MAT2A inhibitor AG-270/S095033 in patients with advanced malignancies: a phase I trial - Mrinal Gounder; Melissa Johnson; Rebecca S. Heist; Geoffrey I. Shapiro; Sophie Postel-Vinay; Frederick H. Wilson; Elena Garralda; Gerburg Wulf; Caroline Almon; Salah Nabhan; Elia Aguado-Fraile; Peng He; et al. (Nature Communications)
Abstract Homozygous MTAP deletion occurs in ~15% of cancers, making them vulnerable to decreases in the concentration of S-adenosylmethionine (SAM). AG-270/S095033 is an oral, potent, reversible inhibitor of methionine adenosyltransferase 2 A (MAT2A), the enzyme primarily responsible for the synthesis of SAM. We report results from the first-in-human, phase 1 trial of AG-270/S095033 as monotherapy in patients with advanced malignancies (ClinicalTrials.gov Identifier: NCT03435250). Eligible patients had tumors with homozygous deletion of CDKN2A/MTAP and/or loss of MTAP protein by immunohistochemistry. Patients received AG-270/S095033 once daily (QD) or twice daily (BID) in 28-day cycles. The primary objective was to assess the maximum tolerated dose (MTD) of AG-270/S095033. Secondary objectives included safety, tolerability, pharmacokinetics (PK), pharmacodynamics (PD), and efficacy. Forty patients were treated with AG-270/S095033. Plasma concentrations of AG-270/S095033 increased with dose. Maximal reductions in plasma SAM concentrations ranged from 54% to 70%. Analysis of paired tumor biopsies showed decreases in levels of symmetrically di-methylated arginine (SDMA) residues. Reversible increases in liver function tests, thrombocytopenia, anemia and fatigue were common treatment-related toxicities. Two partial responses were observed; five additional patients achieved radiographically confirmed stable disease for ≥16 weeks. AG-270/S095033 has a manageable safety profile. Our data provide preliminary evidence of clinical activity and proof-of-mechanism for MAT2A inhibition.